The Significance Of Intertextuality In Anglo-American Literature (Global Scientific Review, 2025)
The importance of one text can be influenced into another one by adding several citations or quotations. The interchange between the culture, the connection among literary authors through the centuries is the sign of the presence of intertextuality. There are visible marks in different works that can be noticed by readers simultaneously